Perfil epidemiológico das internações por malária no estado do Pará: uma análise de um período de 10 anos (2012 a 2022) - LIMA, Cindy Santos de (2024)
Objectives: To describe the epidemiological characteristics of hospitalizations for malaria in the state of Pará from 2012 to 2022. Method: This is an ecological, cross-sectional, descriptive and retrospective study based on the analysis of secondary data from hospital admissions for malaria recorded in the Hospital Information System (SIH) available for consultation in the database of the Unified Health System IT Department (DATASUS). The following variables were considered: number of hospitalizations, year of hospitalization, species of Plasmodium sp., Health Region of residence, sex, race/ethnicity, age group and hospitalization character. Results: Between the years 2012 to 2022 3,821 hospital admissions for malaria were recorded in residents of the state of Pará. Among the years analyzed the year with the highest hospitalizations concentration was 2012 (n = 936; 24.50%) and the lowest was 2021 (n = 108; 2.83%). Regarding the percentage variation between consecutive years the year 2022 presented the largest percentage difference in the number of hospitalizations with growth of 168.52% compared to 2021. The most common etiological agente found in hospitalizations was Plasmodium vivax (n = 2,598; 67.99%), followed by Plasmodium falciparum (n = 377; 9.87%) and Plasmodium malariae (n = 117; 3.06%). The areas with the highest concentration of hospitalizations due to the disease according to Regional Health were distributed in order: Tocantins (n = 866; 22.66%), Araguaia (n = 744; 19.47) and Tapajós (n = 644; 16.85%). Furthermore, the concentration in these areas varied to a greater or lesser extent intensity throughout the years of study. Regarding the profile of these hospitalizations in the region these predominated in males (n = 2361; 61.79%) aged between 20 and 29 years (n= 878; 22.98%), of brown color/race (n = 2,784; 72.86%) and of an urgent nature (99.74%). Conclusion: Agreement with the literature was demonstrated both sociodemographically and in relation to the parasitic agent that causes malaria, as well as alternating periods of decrease in hospitalizations followed by an increase in cases. The health regions with the highest rates of hospitalizations are agreeing with aspects present in the region that would justify the difficulty of eradicating malaria (climate, vegetation, temperature, rainy periods, deforestation generated by non-sustainable economic practices). Several factors involving the COVID-19 pandemic probably contributed to malaria control, as well as underreporting or mistaken and/or late diagnosis, compromising the real reading of the profile of hospitalizations.